Profile of Patients with Gnatoschizis Post Alveolar Bone Graft: A Serial Case Study - Hatibie, Mendy; Oley, Max C.; Aruperes, Marturia I. (Medical Scope Journal, 2025)
Abstract: Gnatoschizis, or cleft alveolus, is a common congenital anomaly in Indonesia. This condition significantly impacts dental and facial development, and often requires alveolar bone grafting to stabilize the maxillary arch, facilitate tooth eruption, and improve facial aesthetics. This was a serial case study involving 11 patients aged 12–18 years with gnatoschizis who underwent alveolar bone grafting using autologous iliac cancellous bone at Prof. Dr. R. D. Kandou Hospital. The results showed that the majority of patients were female, with labiopalatoschizis being the most common type. Surgical procedures included orthodontic preparation, iliac crest bone harvesting, and peri-alar augmentation. Postoperative outcomes demonstrated successful upper dental arch continuity and alar base reconstruction, with minimal donor site morbidity. In conclusion, this study provides valuable insights into the patient profile and clinical outcomes of gnatoschizis post alveolar bone graft. The predominance of female patients and the high incidence of labiopalatoschizis highlight the need for targeted interventions and comprehensive care strategies. A multidisciplinary approach is essential for optimal outcomes. Future research should focus on optimizing treatment protocols and exploring novel therapeutic modalities to further improve patient outcomes. Additionally, long-term follow-up studies are necessary to assess the stability and durability of the surgical outcomes, as well as the overall quality of life of patients with gnatoschizis. Keywords: gnatoschizis; alveolar bone grafting; cleft alveolus